1972
DOI: 10.1079/bjn19720085
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic balance of manganese in young women

Abstract: I . Metabolic balance studies of manganese were made on four young women, using brilliant Retention of an element occurs when the total intake is greater than the total output, and its measurement is dependent upon the accuracy of all experimental procedures. For an element like M n which is believed to be poorly absorbed, calculated retentions of up to 63% of the total intake which have been reported for normal subjects are hardly credible, and are unlikely to be caused solely by an overestimate of the intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 16 publications
4
6
0
Order By: Relevance
“…The mean Mn intake (2.7 mg/d) corresponded very closely with the 2.8 mg/d reported previously for four women in New Zealand (McLeod & Robinson, 1972) and was within the range of 2-4 mg/d provided by the majority of mixed Western diets (Belz, 1960;North, Leichsenring & Norris, 1960;Schroeder, Balassa & Tipton, 1965;Tipton, Stewart & Dickson, 1969;White, 1969;Kirkpatrick & Coffin, 1974). Intakes of less than 2 mg Mn/d were reported by Gormican (1970) and White & Gynne (1971).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mean Mn intake (2.7 mg/d) corresponded very closely with the 2.8 mg/d reported previously for four women in New Zealand (McLeod & Robinson, 1972) and was within the range of 2-4 mg/d provided by the majority of mixed Western diets (Belz, 1960;North, Leichsenring & Norris, 1960;Schroeder, Balassa & Tipton, 1965;Tipton, Stewart & Dickson, 1969;White, 1969;Kirkpatrick & Coffin, 1974). Intakes of less than 2 mg Mn/d were reported by Gormican (1970) and White & Gynne (1971).…”
Section: Discussionsupporting
confidence: 87%
“…Until recently, the only information on the daily intake of trace elements by New Zealand people came from the analysis of constant diets of four young women participating in a balance study (McLeod & Robinson, 1972;Robinson, McKenzie, Thomson & van Rij, 1973). The concentrations of manganese, copper, zinc and cadmium in some New Zealand foods is now known (Guthrie, 1975) but the lack of information on recent food intake and dietary patterns make it difficult to estimate from food concentrations the intakes of the trace elements for people of different ages.…”
mentioning
confidence: 99%
“…Positive balances were observed in two women with respective mean manganese intakes of 2.48 mg/day and 2.62 mg/day for 27 days (McLeod and Robinson, 1978). In another study with 20 men and 20 women, balances did not differ significantly from zero (0.27 ± 1.07 mg/day in men vs. −0.12 ± 0.49 mg/day in women: not statistically different) when subjects consumed a controlled diet providing 3.51 mg/day of manganese (at an energy intake of 2 000 kcal/day) for four weeks (Finley et al, 1994).…”
Section: Balance Studies On Manganesementioning
confidence: 96%
“…The manganese retention rate, similar to absorption rate, was 10.2% for men and 3.7% for women. McLeod and Robinson [17] have reported that the manganese absorption rate was ~ 12% for meatloaf, ice cream, and tea. However, North et al [18] showed that the absorption rate was 50% for the group on a low-protein and high-vegetable diet, while Mena et al [19] indicated that the absorption rate of manganese for healthy adults is only 3 -4%.…”
Section: Discussionmentioning
confidence: 99%